Denitrification in a Soil under Wheat Crop in the Humid Pampas of Argentina - Picone, Liliana; Videla, Cecilia; Picaud, Calypso Lisa; García, Fernando Oscar; Rizzalli, Roberto Héctor (Scientific Research, 2019)
The need to accurately estimate gaseous nitrogen losses from soils is required to have a better understanding of the processes involved as well as soil and environmental conditions, and management practices contributing to these emissions. The objective was to quantify the denitrification rate using undisturbed cores with acetylene, as related to nitrogen (N) fertilization rate in a spring wheat crop (Triticum aestivum L.) under conventional tillage. Soil denitrification losses remained low throughout most of the growing season, when water-filled pore space (WFPS) was below 60%, ranging from 0.79 to 447.3 g N2O-N ha-1•day-1 in the fertilized plot and was less than 47.3 g N2O-N ha-1•day-1 in the control. Denitrification rates were the highest when N fertilizer was applied after frequent and intensive rain. A good correlation was found between the logarithm of the daily denitrification rate and WFPS (r = 0.67, n = 90); however the NO3-N concentration was not a good indicator (r = 0.21, n = 90). Cumulative N2O-N losses by denitrification averaged 3.5 and 0.9 kg N2O-N ha-1 in the fertilized and unfertilized treatment, respectively, during a period of 4 months this difference was not significant. Most N2O-N losses occurred early in the spring; therefore sampling schedules need to focus on this period.